Pengaruh Penyuluhan Tentang Perilaku Seks Pranikah Terhadap Pengetahuan dan Sikap Siswa di SMA Negeri 1 Kayan Hulu Tahun 2023 - Noriyati Noriyat; Sohibun Sohibun; Ria Damayanti; Nurul Khoirun Nisa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The latest data from the Sintang District Health Office for 2022 shows that in the period January-July 2022, according to gender, there were 10 STI cases in women and 23 cases in men.The aim of this study was to determine the effect of counseling on premarital sexual behavior on the knowledge and attitudes of students at SMA Negeri 1 Kayan Hulu in 2023. This study used an quantitative method with a pre-experimental design and used the One Group Pretest-Posttest design Design. The results showed that there was an increase in knowledge after counseling of 1.5 and an increase in attitude after counseling of 3.2. Statistical test results using the Wilcoxon test on the knowledge variable obtained P-value = 0.0001 <0.05 and on the attitude variable obtained P-value = 0.0001 <0.05. This means that there are differences in students' knowledge and attitudes before and after counseling about premarital sex behavior. There is an effect of counseling about premarital sex behavior on the knowledge and attitudes of students at SMA Negeri 1 Kayan Hulu in 2023.